PENYULUHAN FISIOTERAPI PADA SIKAP ERGONOMIS UNTUK MENGURANGI TERJADINYA GANGGUAN MUSCULOSKELETAL DISORDERS (MSDs) DI KOMUNITAS KELUARGA DESA KEBOJONGAN - Nur Susanti; Aida Naurah Septi (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2021)
Musculoskeletal Disorders (MSDs) are complaints that a person feels in the skeletal muscles ranging from very mild to severe complaints. If in this case the muscles receive static loads repeatedly and for a long time, it can cause damage to the muscles, nerves, tendons, joints, cartilages and inter-vertebrate discs. From the observation process of identifying physiotherapy problems in family community  by Lecturer and Physiotherapy Study Program students of the Faculty of Health Sciences, Pekalongan University by interviewing family members, it was found that the problems experienced by family members were disorders of musculoskeletal disorders (MSDs) which were caused by not paying attention ergonomic attitude when doing activities. Situation analysis in the form of observation made by team  in the family community, kebojongan village, comal sub-district, pemalang district in the form of interview with the family community in identifying physiotherapy problems in ergonomic attitudes to redurs using lecture and question and answer methods. The purpose of this activity is to increase knowledge about ergonomic attitudes that can reduce the occurrence of musculoskeletal disorders (MSDs). The solution offered to partners is physiotherapy counseling methods on ergonomics to reduce the occurrence of musculoskeletal disorders (MSDs). The implementation of extension activities was attended by four participants. Before extension, participants were given a pre-test and a post-test was given after counseling was carried out as a measure of participants' understanding of extension. The results of the pre test and post test proved that the level of understanding of the participants increased after physiotherapy counseling. It can be concluded that after being given physiotherapy counseling there is a significant increase in understanding the role of physiotherapy regarding ergonomic attitudes and musculoskeletal disorders (MSDs). Keywords: Ergonomic Attitude, musculoskeletal disorders